Stability of depressive symptoms over 3 months post-partum - Abdollahi, Fatemeh; Zarghami, Mehran; Shariff Ghazali, Sazlina; Lye, Munn Sann (Wiley-Blackwell Publishing, 2015)
Aim: Prolonged depression during the post-partum period is associated with maternal and infant mortality and morbidity. Less attention has been given to factors that predict the persistence of depression beyond the ﬁrst 3 months post-partum.